Vog: Using Volcanic Eruptions to Estimate the Health Costs of Particulates. Issue 620 (1st July 2018) - Halliday, Timothy J; Lynham, John; de Paula, Áureo
Abstract: The negative consequences of long-term exposure to particulate pollution are well established but a number of studies find no effect of short-term exposure on health outcomes. The high correlation of industrial pollutants complicates the estimation of the impact of individual pollutants on health. In this study, we use emissions from Kīlauea volcano, which are uncorrelated with other pollution sources, to estimate the impact of pollutants on local emergency room admissions and a precise measure of costs. A one standard deviation increase in particulates leads to a 23–36% increase in expenditures on ER visits for pulmonary outcomes, mostly among the very young.